Study of Large Ruminants Diversity in Java at Eighth Century Based on Borobudur Temple Reliefs - Hardyta, Galy; Nugrahini, Yosephine Laura Raynardia Esti; Ekarini, Fransiska Dian; Setyowening, Natalia Dewi; Elisa (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2022)
Large ruminants, consisting of cattle and buffalo, have played an important role in human life from the past to the present. Information about the utilization of large ruminants was often found in inscriptions in ancient Java. Unfortunately, the diversity of these large ruminants was not described in detail. The reliefs of the temples can be used as a consideration in understanding the diversity of large ruminants based on the morphological characteristics carved in the reliefs. Borobudur Temple, a historical building from the 8th century AD which was rich in reliefs, can be used as a data source to find information about the diversity of the large ruminants in Java. The aims of this study was to find the diversity of the large ruminants in Java in the 8th century based on the reliefs at Borobudur Temple. The research was conducted by observing various large ruminant images contained in the reliefs of Borobudur Temple. The results of the observations were interpreted and clustered based on their morphological characteristics. The results showed that there were ten relief panels containing images of cattle and nine relief panels containing images of buffalo. Based on the observed morphological characteristics, it could be concluded that there was only one breed of cattle and buffalo, respectively zebu (Bos indicus) and wild buffalo (Bubalus arnee).